The politics of performativity in transcommunication and its communicative/expressive fitness: towards a general outline - Puppel, Stanisław (Scripta Neophilologica Posnaniensia, 2018)
The politics of performativity in transcommunication and its communicative/expressive fitness: towards a general outline